Analisis spasial temporal zona rawan kekeringan lahan pertanian berbasis remote sensing - Agus Suprihatin Utomo; M. Pramono Hadi; Emilya Nurjani (Jurnal Teknosains, 2022)
A mapping model of drought-prone zones for agricultural land based on Geographic Information Systems is needed to determine the distribution of drought vulnerability levels that occured in Bantul Regency, DI Yogyakarta. This study aims to determine the estimated area of agricultural land drought based on the interpretation of aerial images. This study compares the performance of the drought potential index of agricultural land using the Normalized Difference Drought Index (NDDI) algorithm based on remote sensing technology/ Landsat 8 satellite imagery to identify the estimated zones indicated for agricultural land drought that occurred in Bantul Regency, based on trends in spatio-temporal data with recording intervals from the 2015 until 2020 data representative during the dry season. Comparisons were made by looking at the performance between indices extracted from Landsat 8 imagery data based on the value of the green vegetation parameter/ Normalized Difference Vegetation Index (NDVI) and the soil and vegetation moisture parameters/ Normalized Difference Water Index (NDWI). The method used in this research is descriptive correlative method: quantitative and qualitative deductive using geostatistical indicators based on big data analysis to measure and compare various data variables spatio-temporal. The distribution of agricultural land drought through the NDDI index transformation method on a normal, mild, moderate, to severe scale occurs in almost all areas of Bantul Regency. This happened, due to the influence of natural activities of the global climate phenomenon ENSO, the impact of the transition of the El Nino phenomenon to La Nina (wet drought) which was more dominant in 2016. The average area affected by drought in Bantul Regency on a normal scale affected was ± 6.500,49 ha, affected by mild drought was ± 17.192,16 ha, affected by moderate-scale drought was ± 8.636,155 ha, and affected by drought of heavy scale agricultural land was ± 2.407,485 ha.